Intravenous pamidronate in refractory ankylosing spondylitis - García-Poma, Augusto (2007)
Objective: To determine the response of an aminobisphosphonate (pamidronate) in patients with ankylosing spondylitis (AS) who had suboptimal or no response to nonsteroidal anti-inflammatory drugs (NSAIDs) and sulfasalazine. Design: Comparative clinical study. Setting: Hospital Nacional Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Participants: Patients with ankylosing spondylitis. Intervenciones: Nine patients with AS (6 males), with active disease [BASDAI ≥4] and no response to NSAIDs and sulfasalazine up to 3g/day entered the study. All patients received monthly infusions of 60 mg of pamidronate for 6 months and remained taking NSAID and sulfasalazine. Clinical improvement was evaluated using the Assessments in Ankylosing Spondylitis 20 (ASAS 20). Secondary evaluations included ASAS 40, BASDAI 50, BASDAI, BASFI, and BASMI at 24 weeks and at last observation [48 weeks (32 to 86 weeks)]. Differences between pre and post treatment distributions of all continuous indices were evaluated using the Wilcoxon signed rank test. Main outcome measures: Evaluated of ASAS 20. Results: Sixty-seven percent achieved ASAS 20 at 24 weeks and 78% at 48 weeks; 33,3% and 55,6% achieved ASAS 40 at 24 and 48 weeks, respectively, and 33,3% and 44,4% achieved BASDAI 50 at weeks 24 and 48, respectively. One patient relapsed at week 20. In three patients (33,3%) the scores remained unchanged. At weeks 24 and 48 mean BASDAI decreased by 45,1% (p=0,007) and by 52,1% (p=0,01), mean BASFI decreased by 38,2% (p=0,007) and by 52,3% (p=0.007), and mean BASMI decreased by 39,2% (p=0,01) and 39,2% (p=0,01), respectively. There were no significant adverse events with this therapy. Conclusions: Our data provide further evidence of pamidronate therapy effectiveness in patients with AS who are refractory to NSAIDs and sulfasalazine.